Boer Goat Production in Kikatsi Sub County, Kiruhura District, Uganda - Arineitwe, I.; Ndyomugyenyi, E. K. (Livestock Research for Rural Development, 2013)
A study was conducted to assess the contribution of Boer goats to household incomes in Kikatsi Sub County, Kiruhura District. A total of 60 households were used for the study in five different parishes in the sub county. Data were collected using structured questions, observations, and interviews. Secondary sources of data were also reviewed. Respondents (93.4%) who kept between 1and 60 Boer goats were more than those (86.7%) who kept a similar number of indigenous goats. However, there was a small difference of 1.6% between respondents who kept 21 - 40 indigenous goats (43.3%) and those (41.7%) who kept a similar number of Boer goats. The number of Boer goats (78.3%) heavier than 26 kg was higher than that of indigenous goats (51.7%) with similar weights. The market price of the goats was dependent on the weight of the individual goat but not the breed type. Respondents (93.3%) who sold 1 - 4 Boer goats per month were more than those (86.7%) who sold a similar number of indigenous goats indicating that Boer goats contributed more to farmers’ income than indigenous goats. The main limitations to Boer goat production were lack of capital (95%), shortage of established cultivated pasture and fodder crops (90%), poor goat management skills (81.7%), and lack of veterinary services (75%). The other source of income for farmers was cattle keeping (75%) although some farmers (13.3%) also grew crops such as bananas for income generation. The study showed that Boer goats contributed to household incomes and people adopted the new intervention of Boer goat production.
Keywords: breed type, cattle, household incomes, intervention, limitations, market price